Successful ecosystem-based management of Antarctic krill should address uncertainties in krill recruitment, behaviour and ecological adaptation - Meyer, Bettina; Atkinson, Angus; Bernard, Kim S.; Brierley, Andrew S.; Driscoll, Ryan; Hill, Simeon L.; Marschoff, Enrique Ricardo; Maschette, Dale; Perry, Frances A.; Reiss, Christian S.; Rombola, Emilce Florencia; Tarling, Geraint A.; et al. (Communications Earth & Environment)
Antarctic krill, Euphausia superba, supports a valuable commercial fishery in the Southwest Atlantic, which holds the highest krill densities and is warming rapidly. The krill catch is increasing, is concentrated in a small area, and has shifted seasonally from summer to autumn/winter. The fishery is managed by the Commission for the Conservation of Antarctic Marine Living Resources, with the main goal of safeguarding the large populations of krilldependent predators. Here we show that, because of the restricted distribution of successfully spawning krill and high inter-annual variability in their biomass, the risk of direct fishery impacts on the krill stock itself might be higher than previously thought. We show how management benefits could be achieved by incorporating uncertainty surrounding key aspects of krill ecology into management decisions, and how knowledge can be improved in these key areas. This improved information may be supplied, in part, by the fishery itself. Fil: Meyer, Bettina. Alfred-Wegener-Institut, Helmholtz-Zentrum für Polar- und Meeresforschung; Alemania. University of Oldenburg; Alemania Fil: Atkinson, Angus. Plymouth Marine Laboratory; Reino Unido Fil: Bernard, Kim S. State University Of Oregon. College Of Earth, Ocean And Atmospheric Sciences.; Estados Unidos Fil: Brierley, Andrew S. University of St. Andrews; Reino Unido Fil: Driscoll, Ryan. Alfred-Wegener-Institut, Helmholtz-Zentrum für Polar- und Meeresforschung; Alemania Fil: Hill, Simeon L. British Antartic Survey; Reino Unido Fil: Marschoff, Enrique Ricardo. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Maschette, Dale. University of Tasmania; Australia. Australian Antarctic Division; Australia Fil: Perry, Frances A. Plymouth Marine Laboratory; Reino Unido Fil: Reiss, Christian S. Southwest Fisheries Science Center,; Estados Unidos Fil: Rombola, Emilce Florencia. Ministerio de Relaciones Exteriores, Comercio ...